The relationship between diabetes knowledge level, physical activity, and quality of life in older adults - KURU ÇOLAK, TUĞBA; ÖZGÜL, BAHAR (My University, 2023)
Aim: This study aimed to examine the relationship between knowledge about diabetes, physical activity, and quality of life in older adults with type 2 diabetes. Material and Method: A total of 188 geriatric individuals with a mean age of 75.2 years were included in this study. The level of knowledge about diabetes was assessed by the Diabetes Information Questionnaire-24, the Kasari index was used to assess the level of physical activity, and quality of life was assessed by the Diabetes-39 Quality of Life Questionnaire. Results: The participants’ knowledge about diabetes, their physical activity levels according to the Kasari index, and Diabetes-39 quality of life scores were all low. It was determined that level of knowledge was significantly related to physical activity and the Diabetes-39 diabetes control subgroup score (p<0.005). There was a significant relationship between the Kasari index and Diabetes-39 quality of life total score (p<0.005). Conclusion: Level of knowledge about diabetes is related to physical activity and quality of life in elderly adults. It is important to encourage participation in training programs and increase physical activity to improve the quality of life of these individuals, who must live with this chronic disease for many years while also accompanied by geriatric symptoms.

Amaç: Bu çalışmada tip 2 diyabetli yaşlılarda diyabet bilgisi, fiziksel aktivite ve yaşam kalitesi arasındaki ilişkinin incelenmesi amaçlanmıştır. Gereç ve Yöntem: Bu çalışmaya yaş ortalaması 75.2 yıl olan toplam 188 geriatrik birey dahil edilmiştir. Diyabet hakkındaki bilgi düzeyi Diyabet Bilgi Anketi-24 ile, fiziksel aktivite düzeyini değerlendirmek için Kasari indeksi kullanıldı ve yaşam kalitesi Diyabet-39 Yaşam Kalitesi Anketi ile değerlendirildi. Bulgular: Katılımcıların diyabet hakkındaki bilgi düzeyleri, Kasari indeksine göre fiziksel aktivite düzeyleri ve Diyabet-39 yaşam kalitesi skorlarının tümü düşüktü. Bilgi düzeyinin fiziksel aktivite ve Diabetes-39 diyabet kontrol alt grup skoru ile anlamlı düzeyde ilişkili bulunmuştur (p<0.005). Kasari indeksi ile Diabetes-39 yaşam kalitesi toplam puanı arasında anlamlı bir ilişki vardı (p<0.005). Sonuç: Diyabet hakkındaki bilgi düzeyi yaşlı yetişkinlerde fiziksel aktivite ve yaşam kalitesi ile ilişkilidir. Geriatrik semptomların da eşlik ettiği bu kronik hastalıkla uzun yıllar yaşamak zorunda olan bu bireylerin yaşam kalitesini artırmak için eğitim programlarına katılımın teşvik edilmesi ve fiziksel aktivitenin artırılması önemlidir.
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Diabetes Mellitus; Geriatri; Bilgi; Fiziksel aktivite; Yaşam kalitesi; Geriatrics; Knowledge; Physical activity; Quality of life